Limits to growth in elite sport - Some ethical considerations - Breivik, G.
The purpose of this paper is to discuss some of the ethical implications and problems in elite sport as it gets closer to the human performance limit. Modern elite sport must be viewed on the background of the idea of systematic progress. The Olympic motto, 'citius, altius, fortius'-faster, higher, stronger-gives a precise concentration of this idea. Modern sport is also influenced by the liberal idea of a free market where actors can perform, compete and be rewarded according to performance. However, one may ask why and how athletes are willing to risk their health and even their life on the free market of sport when they do the extreme: push limits, break records, set new standards, develop new events. This paper discusses what may be the result as sport moves toward the limits of human performance. The ethical focus on the development of the elite sport should not be restricted to the individual athlete, but should also include the various systems that make up elite sport. Other actors, like coaches, leaders, sponsors, medical personnel, service people, etc., are taking part in the same development. One problem in the modern context is that society is divided into different moral sectors. What is accepted in entertainment or art may not be accepted in sport. It is suggested that we should develop a common ethic for all performance-centered activities like music, painting, science and research, acrobatics and stunts, acting, top politics and business. Or one could include all situations and events where people are put under extreme stress and have to perform well, like during expeditions, in idealistic humanitarian work, during hazards, and catastrophes. At the same time, one should not develop a sort of elite ethic. We need a new ethic that defines the ethical tolerance level in elite sport and that also points to some of the possibilities for development of both character and virtues under extreme pressure.